Preparation and analysis of activated carbon from pomegranate peel for battery applications - M. Selvapandiyan, (Malaysian NANO-An International Journal, 2022)
Currently, natural nontoxic carbon in energy storage systems has attracted much attention because of its scalability, low cost, and microspore nature. Activated carbon has a network of interconnected micro-and mesopores. As a result, the carbon material has a large amount of porosity and specific surface area. The pomegranate peel and activation agent significantly affected the surface area and pore structure. Therefore, a pomegranate peel carbon (PPC) anode material was prepared using a hydrothermal method. The effective carbonization of the pomegranate peel was investigated using scanning electron microscopy. Electrochemical measurements were performed using cycle voltammetry. Powder X-ray diffraction (XRD) analysis was used to investigate the nature of the sample. Scanning electron microscopy (SEM) was used to characterize the morphology of the prepared activated carbon.